Postharvest Loss and Mycofloral Association in Some Culinary Mushrooms in Kathmandu City, Nepal - Adhikari, Hari Sharan; Jha, Sanjay Kumar (Amrit Research Journal, 2020)
Postharvest deterioration of perishable crop is one of the major constrains in food supply. Similar instances are also prevalent in mushrooms. Contamination by fungal pathogens, occurrence of mycotoxins in these goods pose serious health issue. As such, evaluation of mycofloral contamination on commonly grown mushroom namely; Pleurotus sp and Agaricus sp. were made with focus on reducing its postharvest loss. Questionnaire survey to the mushroom growers and mushroom seller of Kathmandu valley was carried out to evaluate the post-harvest losses, causes and management procedure followed by them. Postharvest loss in Agaricus bisporus was higher than in Pleurotus sp., caused by microbial contaminants where extensive use of synthetic fungicides was found. Samples (i.e., Agaricus bisporus, Pleurotus ostreatus and Pleurotus florida) were collected from three major vegetable market of Kathmandu city to detect the mycoflora associated with postharvest deterioration. A total of 21 fungal species belonging to 10 genera were isolated from the samples. The most frequent fungal contaminants were Aspergillus niger (57.77%), Rhizopus sp (42.22 %), Trichoderma viride (34.44%) and Aspergillus flavus (27.77%). As the mushrooms appeared prevailed with many fungal contaminants, more caution should be taken such as selection of strain from resistant varieties, proper sanitation during in-field and postharvest conditions.